Negative electrode material and battery
By adding carbon material to the silicon-based anode material and controlling the distribution of metal compounds, the volume expansion problem of the silicon-based anode material during the circulation process is solved, the first Coulomb efficiency and cycling performance of the battery are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202411850203.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-14
AI Technical Summary
The silicon-based negative electrode material has a severe volume expansion effect during the circulation process, resulting in the material powdering and crushing, the battery's circulation attenuation is fast, and the first time Coulomb efficiency, circulation performance and rate performance are poor.
Using a negative electrode material including silicon-based active substances and carbon materials located on the surface of the silicon-based active substances, the metal M is adjusted by controlling the chromatic difference parameters and the ratio of the strongest characteristic peak half-maximum width of the metal M compound to the characteristic peak half-maximum width of silicon. The mass proportion of compounds reduces side reactions, enhances interface stability, and improves the first-time Coulomb efficiency and specific capacity.
It significantly improves the first Coulomb efficiency, cycle performance and rate performance of the negative electrode material, reduces the expansion efficiency and extends the cycle life of the battery.
Smart Images

Figure CN119315021A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials, and in particular, to negative electrode materials and batteries. Background Art
[0002] Electric new energy vehicles are the future development direction of the automobile market, and their core components are lithium-ion batteries. As the market develops, the demand for high-capacity and high-density batteries is increasing. The use of new high-specific-capacity positive and negative electrode materials is one of the important methods to improve the energy density of batteries.
[0003] More and more new materials such as metals, oxides, and metal alloys are used as active materials in negative electrode materials to continuously explore various ways to improve the energy density of batteries. Taking silicon-based negative electrode materials as an example, silicon-based negative electrode materials, as one of the above active materials, are generally considered to be the next generation of negative electrode materials. They have ultra-high theoretical specific capacity (4200 mAh / g) and low delithiation potential (<0.5 V). The voltage platform of silicon is slightly higher than that of graphite. It is difficult to cause surface lithium deposition during charging, and its safety performance is better. It is highly praised. However, the silicon negative electrode has a drastic volume expansion effect during the cycle process, which causes the material to pulverize and break, and the battery cycle decays quickly. As a high-specific capacity negative electrode material, silicon-oxygen materials have attracted much attention in recent years. The specific capacity of silicon-oxygen materials exceeds 2000 mAh / g, but compared with graphite materials, silicon-oxygen materials have low first coulombic efficiency, poor cycle performance and rate performance. Summary of the invention
[0004] The present application proposes a negative electrode material and a battery, which can comprehensively improve the first coulombic efficiency, cycle performance and rate performance of the negative electrode material.
[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, the silicon-based active material comprising silicon, silicon oxide and a metal M compound; Performing a Lab color difference test on the negative electrode material to obtain the brightness L, red-green color a, and yellow-blue color b of the negative electrode material, wherein 15≤L≤35, -2≤a≤5, and -2≤b≤5; In the XRD spectrum of the negative electrode material, the half-peak width of the strongest characteristic peak in the metal M compound in the negative electrode material is FWHM (M) , the half-peak width of the characteristic peak of the silicon (111) surface is FWHM (Si) , 0.2<FWHM (M) / FWHM (Si) <0.8.
[0006] In some embodiments, 23.5≤L≤35.
[0007] In some embodiments, -0.5≤a≤1.5.
[0008] In some embodiments, -0.5≤b≤1.5.
[0009] In some embodiments, the metal M element includes at least one of Li, Mg, Al, Ti and Cu.
[0010] In some embodiments, FWHM (M) >0.2; and / or, FWHM (Si) >0.2.
[0011] In some embodiments, the metal M compound includes at least one of a metal silicide and a metal silicate.
[0012] In some embodiments, the mass content of the metal M element in the negative electrode material is m M %,2.0≤m M ≤15.
[0013] In some embodiments, the negative electrode material is tested by X-ray photoelectron spectroscopy, and the surface of the negative electrode material has at least one oxygen-containing group selected from CO, C=O, and COO-.
[0014] In some embodiments, the negative electrode material is tested by infrared spectroscopy, and the surface of the negative electrode material has at least one functional group of OH and CH.
[0015] In some embodiments, the silicon oxide includes silicon and oxygen, and the atomic ratio of the silicon to the oxygen is 0 to 2, excluding 0; In some embodiments, the carbon material includes at least one of amorphous carbon and graphitized carbon.
[0016] In some embodiments, the chemical formula of the silicon oxide is SiO x , where 0<x≤2.
[0017] In some embodiments, the median particle size D of the negative electrode material is 50 4μm~9μm; In some embodiments, the specific surface area of the negative electrode material is 0.5 m 2 / g~3.0m 2 / g; In some embodiments, the powder conductivity of the negative electrode material under a pressure of 20 KN is 0.2 S / cm to 10.0 S / cm.
[0018] In some embodiments, the tap density of the negative electrode material is 0.75 g / cm 3~2.00g / cm 3 .
[0019] In some embodiments, the mass content of carbon in the negative electrode material is m C %,2≤m C ≤15.
[0020] In some embodiments, the mass percentage of water in the negative electrode material is m 水 %,0.01≤m 水 ≤0.1.
[0021] In some embodiments, the carbon material located on at least a portion of the surface of the silicon-based active material forms a carbon layer, and the thickness of the carbon layer is 50 nm to 1000 nm.
[0022] In a second aspect, the present application provides a battery comprising the negative electrode material as described in the first aspect.
[0023] The technical solution of this application has at least the following beneficial effects: The negative electrode material provided in the present application includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance. In the present application, through the color difference test, the brightness L, red-green color a, and yellow-blue color b of the negative electrode material satisfy the following relationship: 15≤L≤35, -2≤a≤5, -2≤b≤5. Due to the color difference between the carbon material and silicon, silicon oxide, and metal M compound, when the carbon material completely covers the silicon-based active substance, the brightness L of the negative electrode material decreases; when there is too little carbon material on the surface of the silicon-based active substance, the a value and b value of the negative electrode material are too high. The present application controls the color difference parameters of the negative electrode material and coordinately controls the ratio of the strongest characteristic peak half-width of the metal M compound in the negative electrode material to the characteristic peak half-width of silicon in the negative electrode material within the range of 0.2 to 0.8, thereby adjusting the mass proportion of the metal M compound in the silicon-based active material. Since the metal M compound is inert, under the synergistic effect of an appropriate amount of the metal M compound and the carbon material, the side reaction between the silicon-based active material (especially silicon and silicon oxide) and the electrolyte can be reduced, the consumption of active lithium ions can be reduced, the interface stability of the negative electrode material in contact with the electrolyte can be enhanced, the first coulomb efficiency and specific capacity of the negative electrode material can be improved, and the expansion efficiency of the negative electrode material can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application. DETAILED DESCRIPTION
[0025] In order to better illustrate the present application and facilitate understanding of the technical solution of the present application, the present application is further described in detail below. However, the following embodiments are only simple examples of the present application and do not represent or limit the scope of protection of the present application. The scope of protection of the present application shall be subject to the claims.
[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0027] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, the silicon-based active material comprising silicon, silicon oxide and a metal M compound; Performing a Lab color difference test on the negative electrode material to obtain the brightness L, red-green color a, and yellow-blue color b of the negative electrode material, wherein 15≤L≤35, -2≤a≤5, and -2≤b≤5; In the XRD spectrum of the negative electrode material, the half-peak width of the strongest characteristic peak in the metal M compound in the negative electrode material is FWHM (M) , the half-peak width of the characteristic peak of the silicon (111) surface is FWHM (Si) , 0.2<FWHM (M) / FWHM (Si) <0.8.
[0028] The negative electrode material provided in the present application includes a silicon-based active substance and a carbon material located on at least a portion of the surface of the silicon-based active substance. In the present application, through the color difference test, the brightness L, red-green color a, and yellow-blue color b of the negative electrode material satisfy the following relationship: 15≤L≤35, -2≤a≤5, -2≤b≤5. Due to the color difference between the carbon material and silicon, silicon oxide, and metal M compound, when the carbon material completely covers the silicon-based active substance, the brightness L of the negative electrode material decreases; when there is too little carbon material on the surface of the silicon-based active substance, the a value and b value of the negative electrode material are too high. The present application controls the color difference parameters of the negative electrode material and coordinately controls the ratio of the strongest characteristic peak half-width of the metal M compound in the negative electrode material to the characteristic peak half-width of silicon in the negative electrode material within the range of 0.2 to 0.8, thereby adjusting the mass proportion of the metal M compound in the silicon-based active material. Since the metal M compound is inert, under the synergistic effect of an appropriate amount of the metal M compound and the carbon material, the side reaction between the silicon-based active material (especially silicon and silicon oxide) and the electrolyte can be reduced, the consumption of active lithium ions can be reduced, the interface stability of the negative electrode material in contact with the electrolyte can be enhanced, the first coulomb efficiency and specific capacity of the negative electrode material can be improved, and the expansion efficiency of the negative electrode material can be reduced.
[0029] It should be noted that the color difference between silicon-based active materials and carbon materials is quite different. The color of metal M compounds tends to be bluish green, the color of silicon oxide is yellow-brown, and the color of carbon materials is black. When there is too much carbon material on the surface of the silicon-based active material, the brightness and red-green color a, and yellow-blue color b measured by the color difference model are greatly affected by the carbon material. When there is too little carbon material on the surface of the silicon-based active material, the red-green color a, and yellow-blue color b measured by the color difference model are greatly affected by the silicon-based active material. At the same time, the results of the color difference model are related to the state of the surface carbon material of the negative electrode material. In addition, the type and physicochemical properties of the carbon material on the surface of the silicon-based active material will also affect the color difference data. Specifically, carbon materials include those with sp 2 Hybrid orbitals of carbon atoms and sp 3 Hybrid orbital carbon atoms, when sp 3 When the molar proportion of hybridized carbon atoms is high and the carbon material is mainly disordered carbon, the color of the carbon material is gray, and the overall brightness of the negative electrode material will increase. 3 When the molar proportion of hybridized carbon is small and the carbon material is mainly disordered structural carbon, the color of the carbon material tends to be black, and the brightness of the negative electrode material will decrease. Therefore, after the silicon-based active material is coated with the carbon material, the brightness of the negative electrode material will also change, and the red-green color a and the yellow-blue color b will also change accordingly.
[0030] In some embodiments, the negative electrode material I D / I G In the range of 0.4~3.0, I D / I G Specifically, it can be 0.4, 0.5, 0.8, 1.0, 1.2, 1.5, 2.0, 2.3, 2.5, 2.8 or 3.0, etc., and of course, it can also be other values within the above range, which are not limited here. D with I G Can represent respectively with sp 3 Hybrid orbitals of carbon atoms and sp 2 The number of carbon atoms in the hybrid orbital. 2 When the molar proportion of hybridized carbon atoms is high, I D / I G On the contrary, when the sp 3 When the molar proportion of hybridized carbon atoms is high, I D / I G In this application, the I of the negative electrode material is controlled D / I G The ratio is controlled within the above range, which is beneficial to regulating the sp 3The molar content of hybridized carbon atoms is beneficial to controlling the brightness L, red-green color a, and yellow-blue color b of the negative electrode material within a reasonable range.
[0031] In some embodiments, the negative electrode material is subjected to a Lab color difference test, and the brightness L of the negative electrode material is 15≤L≤35. L can be 15, 18, 20, 25, 28 or 35, etc., and of course it can also be other values within the above range, which are not limited here. The brightness L of the negative electrode material mainly depends on the distribution uniformity of the carbon material on the surface of the silicon-based active material, preferably, 23.5≤L≤35.
[0032] In some embodiments, the negative electrode material is subjected to a Lab color difference test, and the red-green color a and yellow-blue color b of the negative electrode material are -2≤a≤5, and -2≤b≤5. a and b can be -2, -1.5, -1.2, -1.0, -0.5, -0.2, 0.1, 0.15, 0.18, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5, respectively. Of course, other values within the above ranges can also be used, which are not limited here. The red-green color a and yellow-blue color b of the negative electrode material mainly depend on the exposure degree of the silicon-based active material. As the exposure area decreases, the red-green color a and yellow-blue color b will also decrease. Preferably, -0.5≤a≤1.5, -0.5≤b≤1.5.
[0033] In some embodiments, the silicon-based active material includes silicon, silicon oxide, and a metal M compound.
[0034] In some embodiments, silicon oxide includes silicon and oxygen, and the atomic ratio of silicon to oxygen is 0 to 2, excluding 0. The atomic ratio of silicon to oxygen can be 0.05, 0.11, 0.21, 0.26, 0.31, 0.41, 0.51, 0.59, 0.61, 0.69, 0.71, 0.74, 0.76, 0.79, 0.89, 0.99, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 and 2, etc., which are not limited here. Preferably, the atomic ratio of silicon to oxygen is 0 to 1, excluding 0.
[0035] In some embodiments, the chemical formula of silicon oxide is SiO x, where 0 < x ≤ 2, and x can specifically be 0.05, 0.11, 0.21, 0.26, 0.31, 0.41, 0.51, 0.59, 0.61, 0.69, 0.71, 0.74, 0.76, 0.79, 0.89, 0.99, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc., which are not limited herein. Preferably, 0 < x < 1. The silicon oxide can be a material formed by silicon particles dispersed in SiO2; or it can be a material having a tetrahedral structural unit, with a silicon atom located at the center of the tetrahedral structural unit and oxygen atoms and / or silicon atoms located at the four vertices of the tetrahedral structural unit.
[0036] In some embodiments, the compound of metal M includes at least one of metal silicide and metal silicate.
[0037] In some embodiments, the metal M includes at least one of Li, Mg, Al, Ti, and Cu.
[0038] In some embodiments, the metal silicate includes at least one of lithium silicate, magnesium silicate, aluminum silicate, lithium magnesium silicate, lithium aluminum silicate, and lithium aluminum titanium silicate.
[0039] In some embodiments, FWHM (M) / FWHM (Si) can specifically be 0.21, 0.22, 0.25, 0.28, 0.3, 0.4, 0.5, 0.6, 0.7, 0.79, etc. Of course, it can also be other values within the above range, which are not limited herein. When the ratio of FWHM (M) / FWHM (Si) is too large, the amount of metal M compound in the negative electrode material increases, the capacity of the negative electrode material decreases, and the defects and pores caused by metal M during the reduction of silicon oxide also increase, resulting in a significant increase in the contact reaction sites between the negative electrode material and the electrolyte, an aggravation of side reactions, and a decrease in the first Coulombic efficiency of the negative electrode material. When the ratio of FWHM (M) / FWHM (Si) is too small, the amount of metal M compound in the negative electrode material decreases, the mass ratio of silicon and silicon oxide increases, the side reaction between silicon and the electrolyte is aggravated, the gas generation during charge and discharge is aggravated, and the first efficiency and cycle stability of the battery decrease.
[0040] In some embodiments, in the XRD pattern of the negative electrode material, the full width at half maximum of the strongest characteristic peak in the metal M compound of the negative electrode material is FWHM (M) , and the full width at half maximum of the characteristic peak of the silicon (111) plane is FWHM (Si) , FWHM (M) > 0.2, FWHM (M)>0.2. Specifically, FWHM (M) Specifically, it can be 0.21, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, etc. FWHM (Si) Specifically, it can be 0.26, 0.3, 0.5, 0.8, 1.0, 1.2, 1.4, 1.5, 1.6, 1.7, etc., and is not limited here.
[0041] In some embodiments, the mass content of the metal M element in the negative electrode material is m M wt%,2.0≤m M ≤15, the mass content of the metal M element can be 2 wt%, 5 wt%, 6 wt%, 8 wt%, 10 wt%, 12 wt%, 13 wt%, 14 wt% or 15 wt%, etc., and of course it can also be other values within the above range, which is not limited here. When the mass content of the metal M in the negative electrode material is controlled within the above range, it is beneficial to improve the first coulombic efficiency and cycle stability of the negative electrode material.
[0042] In some embodiments, the carbon material includes at least one of amorphous carbon and graphitized carbon. Preferably, the carbon material includes amorphous carbon, which may be soft carbon or hard carbon, and the graphitized carbon may be diamond-like carbon, high-temperature carbide, etc. Compounding amorphous carbon and silicon-based active materials can comprehensively improve the conductivity of the negative electrode material and reduce expansion.
[0043] In some embodiments, the mass content of carbon in the negative electrode material is m C %,2≤m C ≤15, the mass content of carbon element can specifically be 2%, 5%, 6%, 8%, 10%, 12%, 13%, 14% or 15%, etc., of course, it can also be other values within the above range, which is not limited here.
[0044] In some embodiments, the mass percentage of water in the negative electrode material is m 水 %,0.01≤m 水 ≤0.05;m 水 Specifically, it can be 0.01%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045% or 0.05%, etc. Of course, it can also be other values within the above range, which is not limited here.
[0045] In some embodiments, at least part of the carbon material located on the surface of the silicon-based active material forms a carbon layer. The carbon material can be located on the surface of the silicon-based active material, or the silicon-based active material and the carbon material particles can be secondary granulated and coated to form secondary particles, which is not limited here. The presence of the carbon layer can reduce the occurrence of side reactions between the negative electrode material and the electrolyte, reduce the consumption of active lithium ions, improve the first effect and low temperature performance of the negative electrode material, and reduce the expansion rate of the negative electrode material.
[0046] In some embodiments, the thickness of the carbon layer is 50nm~1000nm, specifically 50nm, 80nm, 100nm, 150nm, 200nm, 400nm, 500nm, 700nm, 800nm, 900nm, 1000nm, etc., which are not limited here. If the carbon layer is too thick, the carbon content is too high, which is not conducive to obtaining a negative electrode material with a high specific capacity; if the carbon layer is too thin, it is not conducive to increasing the conductivity of the negative electrode material and the volume expansion inhibition performance of the material is weak, resulting in poor long cycle performance. Preferably, the thickness of the carbon layer is 50nm~800nm; more preferably, the thickness of the carbon layer is 100nm~500nm.
[0047] In some embodiments, the negative electrode material is tested by X-ray photoelectron spectroscopy, and the surface of the negative electrode material has at least one oxygen-containing group selected from CO, C=O and COO-. In the present application, since the surface of the negative electrode material has oxygen-containing groups, the oxygen-containing groups can enhance the binding ability of the negative electrode material with the polar solvent in the electrolyte, which is beneficial to improve the transmission efficiency of lithium ions. The non-polar carbon layer is beneficial to the rapid infiltration of the solvated lithium ions in the electrolyte by the negative electrode material, thereby improving the transmission efficiency of lithium ions.
[0048] In some embodiments, the negative electrode material is tested by infrared spectroscopy, and the surface of the negative electrode material has at least one functional group of OH and CH. In the present application, the presence of these functional groups makes the surface of the negative electrode material have polarity differences, thereby adjusting the deposition state after the electrolyte is degraded and enhancing the interface stability of the negative electrode material in contact with the electrolyte.
[0049] In some embodiments, the median particle size D of the negative electrode material is 50 It is 4μm~9μm, specifically can be 4μm, 5μm, 5.5μm, 6μm, 7μm, 8μm, 8.5μm or 9μm, etc., which is not limited here.
[0050] In some embodiments, the specific surface area of the negative electrode material is 0.5 m 2 / g ~3.0 m 2 / g; specifically, 0.5m 2 / g, 0.6 m 2 / g, 0.8 m 2 / g, 1.0 m2 / g, 1.5 m 2 / g, 1.8 m 2 / g, 2.0 m 2 / g, 2.5 m 2 / g, 2.8 m 2 / g or 3.0m 2 / g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Controlling the specific surface area of the negative electrode material within the above range is conducive to improving the first coulombic efficiency of the negative electrode material. When the specific surface area of the negative electrode material is too large, the side reactions between the negative electrode material and the electrolyte increase, which will consume more active lithium ions and reduce the first coulombic efficiency of the negative electrode material.
[0051] In some embodiments, the tap density of the negative electrode material is 0.75 g / cm 3 ~ 2.00g / cm 3 The tap density of the negative electrode material can be specifically 0.75 g / cm 3 , 0.85 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 , 1.4 g / cm 3 , 1.3g / cm 3 , 1.5 g / cm 3 , 1.6 g / cm 3 , 1.8 g / cm 3 or 2.0g / cm 3 Etc., no limitation is made here.
[0052] In some embodiments, the powder conductivity of the negative electrode material under a pressure of 20KN is 0.2 S / cm to 15.0 S / cm, specifically 0.2 S / cm, 0.5 S / cm, 1 S / cm, 2 S / cm, 3 S / cm, 5 S / cm, 6 S / cm, 7 S / cm, 8 S / cm, 10 S / cm or 15 S / cm, etc., and of course, it can also be other values within the above range, which are not limited here. The powder conductivity of the negative electrode material is good, which is conducive to improving the cycle performance of the negative electrode material. When the powder conductivity of the negative electrode material is too small, the structure of the negative electrode material is looser or the conductive network is worse, and the cycle stability is reduced.
[0053] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps: S10, subjecting the mixture of silicon oxygen raw material and dopant to solid phase pre-reaction, wherein the temperature of the solid phase pre-reaction adopts a step-by-step heating process, and exhausts and releases the dopant byproduct gas to obtain a pre-reaction product, wherein the step-by-step heating process includes a first heating stage, a heat preservation stage and a second heating stage, wherein the heating rate of the first heating stage is 1°C / min~3°C / min, and the heating time is 4 hours~12 hours; the temperature of the heat preservation stage is 300°C~400°C, and the heat preservation time is 3 hours~6 hours; the temperature of the second heating stage is 700°C~1200°C, and the heating time is 1 hour~2 hours; S20, subjecting the pre-reaction product to high temperature and high pressure heat treatment to obtain a precursor; wherein the heat treatment pressure is 100-200 MPa, the heat treatment temperature is 800-1200° C., and the heat treatment time is 6-18 hours; S30, placing the precursor in a surface impregnation liquid for thorough mixing, and performing solid-liquid separation to obtain a composite; S40, coating the composite with a liquid coating solution containing a benzene ring carbon source, and drying to obtain a negative electrode material.
[0054] In the present application, a mixture of silicon oxygen raw material and dopant is first subjected to solid phase pre-reaction. The temperature of the solid phase pre-reaction adopts a step-temperature rise process. At the initial stage of the step-temperature rise process, the dopant can be adsorbed on the surface of the silicon source raw material. As the solid phase pre-reaction temperature increases, the doping depth gradually increases, which can improve the dispersion uniformity of the dopant. Then the pre-reaction product is subjected to high temperature and high pressure heat treatment. Through high pressure and high temperature reaction, the solid phase reaction makes the doping material fully contact, which can make the dopant and the silicon oxygen raw material fully react and increase the depth of the solid phase reaction; the high pressure and high temperature reaction can modify the surface of the precursor, eliminate the nanostructure with weak strength on the surface of the precursor, reduce the pore structure on the surface, and form a high-density surface; then the precursor is placed in the surface impregnation liquid for mixing, so that the organic carbon source in the surface impregnation liquid can be adsorbed on the surface of the precursor to modify the surface defects of the precursor; finally, the composite is coated with a liquid coating liquid containing a benzene ring carbon source. After the surface defects of the composite adsorb the benzene ring carbon source, the surface defects can be effectively reduced, and the surface integrity of the negative electrode material can be ensured. In addition, the benzene ring carbon source can be well embedded in the graphitized carbon layer formed after carbonization, thereby improving the optical reflectivity of the surface of the negative electrode material and improving the conductivity of the negative electrode material. The negative electrode material prepared by the preparation method of the present application has excellent first coulomb efficiency, cycle performance and safety. By coating the composite with a liquid coating solution containing a benzene ring carbon source, the carbon layer formed can adjust the sp 3 The molar content of carbon atoms is adjusted, and the physicochemical properties of the carbon layer are adjusted, so that the changes in the carbon layer composition and the changes in the core crystal form work together, while ensuring the conductivity and structural stability of the negative electrode material, the coulombic efficiency and cycle performance of the negative electrode material are improved.
[0055] Before step S10, the method further includes selecting a silicon-oxygen raw material with a suitable particle size, wherein the median particle size of the silicon-oxygen raw material is 4 μm to 9 μm.
[0056] In some embodiments, the mass ratio of the dopant to the silicon oxide raw material is (2~15):100, specifically 2:100, 2.5:100, 5:100, 7.5:100, 10:100, 12.5:100 or 15:100, etc., and of course it can also be other values within the above range, which are not limited here. Too little doping metal will result in too little metal-containing compounds in the negative electrode material, increase the alkalinity of the negative electrode material, increase gas production during charging and discharging, and reduce the first efficiency and cycle stability of the battery. When too much metal is doped, the inert metal compounds in the negative electrode material increase, the capacity of the negative electrode material decreases, and the defects and pores caused by the metal M when reducing silicon oxide will also increase, which significantly increases the contact reaction sites between the negative electrode material and the electrolyte, intensifies the side reactions, and reduces the first coulombic efficiency of the negative electrode material.
[0057] In some embodiments, the mixing process of the dopant and the silicon-oxygen raw material is carried out in a protective gas atmosphere. Specifically, normal pressure stirring can be used, the stirring rate is controlled to be 500 r / min-1000 r / min, and the stirring time is 30min-180min.
[0058] In some embodiments, the stirring rate may be 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min. Of course, it may also be other values within the above range, which is not limited here.
[0059] In some embodiments, the stirring time is 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 120 min, 150 min, 160 min or 180 min, etc., and of course it can also be other values within the above range, which is not limited here.
[0060] It can be understood that by fully stirring, a basic reaction contact interface is provided for each component in the mixture, so that uniform doping of the dopant between the silicon-oxygen raw material particles is achieved, thereby improving the uniformity of the mixture.
[0061] S10, subjecting a mixture of silicon-oxygen raw materials and dopants to a solid-phase pre-reaction, wherein the temperature of the solid-phase pre-reaction adopts a step-by-step temperature increase process to obtain a pre-reaction product.
[0062] In some embodiments, the silicon oxygen raw material includes Si, SiO y Mixture of SiO2 and SiO yAt least one of a mixture of Si and Si, and a mixture of Si and SiO2, wherein 0<y<2.
[0063] In some embodiments, the silicon-oxygen raw material may further include a carbon material, that is, a composite of a silicon-oxygen raw material and a carbon material.
[0064] In some embodiments, the step temperature rise process includes a first heating stage, a heat preservation stage and a second heating stage, wherein the heating rate of the first heating stage is 1°C / min~3°C / min, which is a slow heating state.
[0065] In some specific embodiments, the first heating stage may be, for example, 100°C-150°C-200°C-250°C, and the temperature is maintained for 1 hour to 3 hours in each stage.
[0066] In some embodiments, when the temperature of the insulation stage is 300° C. to 400° C., the insulation time is 3 hours to 6 hours. During the insulation stage, each component of the mixture undergoes sufficient solid phase pre-reaction.
[0067] In some embodiments, the temperature in the insulation stage can be 300°C, 310°C, 320°C, 350°C, 360°C, 380°C or 400°C, and the insulation time can be 3 hours, 3.5 hours, 4 hours, 4.5 hours or 6 hours, etc., which is not limited here.
[0068] In some embodiments, the solid phase pre-reaction is performed under an inert gas.
[0069] In some embodiments, the solid phase pre-reaction is carried out under stirring at a stirring rate of 1000-2000 r / min. The stirring rate can specifically be 1000 r / min, 1200 r / min, 1500 r / min, 1800 r / min or 2000 r / min. Of course, it can also be other values within the above range, which is not limited here.
[0070] In some embodiments, during the second heating stage, stirring of the mixture is stopped, and the temperature is raised to between 700° C. and 1200° C., and after the temperature stabilizes, the mixture is kept at this temperature for 1 to 2 hours, and the dopant gas is exhausted to release.
[0071] In some embodiments, the heating temperature of the second heating stage can be 700°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C or 1200°C, etc., and the insulation time is 1 hour, 1.2 hours, 1.5 hours, 1.8 hours or 2 hours, etc., which is not limited here.
[0072] In the present application, the mixture is subjected to a solid-phase pre-reaction at a relatively low temperature, so that the two solid phases can be further dispersed with each other. At this time, the depth of the solid-phase pre-reaction is shallow, and sufficient solid-phase pre-reaction allows the dopant to be further dispersed between the silicon-oxygen raw material particles, and chemically adsorbed on the surface of the pre-reactant, thereby preventing a single silicon-oxygen material particle from over-reacting and causing the doped metal content to be too high, thereby improving the dispersion uniformity of the doped metal. In addition, in the second heating stage, part of the excess dopant can be vaporized and the dopant gas can be released, preventing the generation of bubbles in the subsequent reaction process, causing pores inside the negative electrode material particles, and improving the density of the negative electrode material.
[0073] S20, subjecting the pre-reaction product to high temperature and high pressure heat treatment to obtain a precursor.
[0074] In some embodiments, the heat treatment pressure is 100 MPa to 200 MPa, and specifically may be 100 MPa, 120 MPa, 140 MPa, 150 MPa, 160 MPa, 180 MPa, 190 MPa or 200 MPa, etc., and may also be other values within the above range, which is not limited here.
[0075] In some embodiments, the heat treatment temperature is 800°C~1200°C, specifically 800°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, etc., and of course it can also be other values within the above range, which is not limited here.
[0076] In some embodiments, the duration of the heat treatment is 6 h to 18 h, specifically 6 h, 8 h, 10 h, 12 h, 15 h, 16 h or 18 h, etc., and of course it can also be other values within the above range, which is not limited here.
[0077] Through high pressure and high temperature reaction, the solid phase reaction makes the silicon oxygen raw material fully contact and react with the dopant, accelerates the reaction of each element in the solid phase reaction process, and increases the depth of the solid phase reaction, so that the solid phase raw material is fully fused to form a uniform reaction powder. In addition, the high pressure and high temperature reaction can modify the surface of the precursor, eliminate the weak nanostructure on the surface of the precursor, reduce the pore structure on the surface, and form a high-density surface; this high-density surface helps to form a stable SEI, which is beneficial to control the infiltration rate of the electrolyte slurry on the negative electrode material, reduce the occurrence of side reactions, reduce the consumption of electrolyte during the cycle, and improve the cycle stability. The uniform silicon-based active material core formed after this high-pressure treatment can enable the negative electrode material to achieve uniform expansion during the charge and discharge process, which is beneficial to the dispersion of expansion stress, greatly reduce the expansion of the negative electrode plate, and is beneficial to improve the first coulomb efficiency, cycle performance and safety of the negative electrode material.
[0078] In some embodiments, the method further comprises crushing and classifying the precursor to reduce agglomeration of the precursor while controlling the precursor to be within an optimized particle size range.
[0079] S30, placing the precursor in a surface impregnation liquid for thorough mixing, and performing solid-liquid separation to obtain a composite.
[0080] In some embodiments, liquid asphalt is dissolved in anhydrous ethanol under stirring to prepare a surface impregnation liquid, and the surface impregnation liquid is filtered to remove impurities.
[0081] In some embodiments, the mass ratio of liquid asphalt to anhydrous ethanol is (1~10):(90~99), specifically 1:99, 2:98, 4:96, 5:95, 6:94, 8:92, 9:91 or 10:90, etc., and of course it can also be other values within the above range, which is not limited here.
[0082] In some embodiments, the dispersed precursor is placed in a surface impregnation liquid, and the mass ratio of the precursor to the surface impregnation liquid is 1:(0.8~1.5), specifically 1:0.8, 1:1.0, 1:1.2, 1:1.3, 1:1.4 or 1:1.5, etc., and of course it can also be other values within the above range, which is not limited here.
[0083] In some embodiments, the mixing of the precursor and the surface impregnation liquid is carried out under stirring, and the stirring rate is 2500r / min~3500r / min, and the stirring time is 30min~90min. Specifically, the stirring rate is 2500r / min, 2600r / min, 2800r / min, 3000r / min, 3200r / min or 3500r / min, and the stirring time is 30min, 45min, 60min, 75min, 90min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0084] In some embodiments, the fully mixed product is sealed and left to stand for 6 to 24 hours, specifically 6 hours, 7 hours, 9 hours, 12 hours, 16 hours or 24 hours, etc., which are not limited here. After the material is completely deposited and layered, it is filtered to separate the solid and liquid and remove the solvent.
[0085] In some embodiments, the method of removing the solvent may include drying.
[0086] In some embodiments, the solvent can be dried in a vacuum oven at a drying temperature of 50°C to 90°C for a drying time of 12h to 240h. The drying temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, and the drying time can be 12h, 15h, 16h, 18h, 20h, 22h or 24h, etc., and of course, other values within the above range can also be used, which are not limited here.
[0087] In the present application, by mixing the precursor with the surface impregnation liquid, the organic carbon source in the surface impregnation liquid can be adsorbed on the surface of the precursor, especially the surface of the tiny defects caused by the precursor during the crushing process, which can further improve and supplement the surface of the precursor and modify the surface defects of the precursor, thereby helping to reduce the occurrence of side reactions between the negative electrode material and the electrolyte.
[0088] S40, coating the composite with a liquid coating solution containing a benzene ring carbon source, and drying to obtain a negative electrode material.
[0089] In some embodiments, the composite is subjected to surface carbon coating and surface modification using a plasma enhanced chemical vapor deposition process. Plasma enhanced CVD can improve the carbon source dissociation efficiency, thereby achieving a wider preferred deposition temperature.
[0090] In some embodiments, the benzene ring-containing carbon source includes at least one of benzene, toluene, ethylbenzene, xylene and phenol.
[0091] In some embodiments, the liquid coating solution includes a benzene ring-containing carbon source and a volatile solution, that is, the benzene ring-containing carbon source is volatilized out by the volatile solution, and the volatile solution includes at least one of ethanol, acetone and butanol.
[0092] In some embodiments, in the liquid coating solution, the mass ratio of the benzene ring-containing carbon source to the volatile solution is 1:(1-2), specifically 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.6, 1:1.8, 1:2, etc., and of course, it can also be other values within the above range, which is not limited here.
[0093] In some embodiments, the pressure during plasma enhanced chemical vapor deposition is controlled at 1000 Pa ~ 5000 Pa, specifically 1000 Pa, 1500 Pa, 2000 Pa, 2500 Pa, 3000 Pa, 3500 Pa, 4000 Pa, 4500 Pa or 5000 Pa, etc., and of course it can also be other values within the above range, which is not limited here.
[0094] In some embodiments, the deposition temperature during plasma enhanced chemical vapor deposition is 400°C~600°C, specifically 400°C, 450°C, 480°C, 500°C, 550°C, 580°C or 600°C, etc., and of course it can also be other values within the above range, which is not limited here.
[0095] In some embodiments, the deposition time during plasma enhanced chemical vapor deposition is 1.0 h to 3.0 h, specifically 1.0 h, 1.5 h, 2.0 h, 2.5 h, 2.8 h or 3.0 h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0096] In some embodiments, before plasma enhanced chemical vapor deposition, the composite is preheated, and the heating temperature is controlled between 65°C and 85°C, specifically 65°C, 70°C, 75°C, 80°C or 85°C, etc., and of course other values within the above range are also possible, which are not limited here.
[0097] In the above scheme, after the surface defects of the composite adsorb the benzene ring-containing carbon source, carbonization is carried out at high temperature. During the carbonization process, the benzene ring-containing carbon source shrinks and releases oxygen sources such as carbon dioxide. Although the defects are difficult to fill completely, supplementary deposition of trace gas-phase carbon sources can effectively reduce surface defects and ensure the surface integrity of the negative electrode material. In addition, the benzene ring-containing carbon source can be well embedded in the graphitized carbon material formed after carbonization, thereby improving the optical reflectivity of the surface of the negative electrode material and improving the conductivity of the negative electrode material.
[0098] An embodiment of the present invention further provides a battery, Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.
[0099] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101 .
[0100] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 includes a positive electrode active material, which includes a compound that can reversibly embed and de-embed metal ions.
[0101] In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.
[0102] In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).
[0103] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.
[0104] In some embodiments, the negative electrode current collector 201 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0105] In some embodiments, the negative electrode active material layer 202 includes a negative electrode material, and the negative electrode material is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method.
[0106] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0107] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0108] Test method: 1) Particle size of negative electrode material: The particle size test method refers to GB / T 19077-2016. The volume-based cumulative particle size distribution of the particles is measured by laser diffraction method. D10 represents the particle size corresponding to 10% of the cumulative particle size distribution of the powder volume, D50 represents the particle size corresponding to 50% of the cumulative particle size distribution of the powder volume, and D90 represents the particle size corresponding to 90% of the cumulative particle size distribution of the powder volume.
[0109] 2) Test method for specific surface area of negative electrode material: Under constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the monolayer adsorption amount of the sample is obtained based on the Brownauer-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of the material.
[0110] 3) Test method for mass content of carbon element in negative electrode material: Thermogravimetric analysis was used to test the mass content of carbon element.
[0111] 4) Test method for the mass content of oxygen in negative electrode materials: An oxygen, nitrogen and hydrogen analyzer was used to test the mass content of oxygen in the negative electrode material.
[0112] 5) Test method for mass content of M element in negative electrode material: The negative electrode material was burned at 750°C in an oxygen-containing atmosphere to constant weight, and then dissolved with a mixed acid consisting of concentrated HF, concentrated HCl, and concentrated HNO3 until the solution no longer produced bubbles. The mixed acid was added twice, and when the solution still had no bubbles, the digestion solution of the negative electrode material was obtained by solid separation. The mass content of M element in the digestion solution was tested by electrically coupled plasma atomic emission spectrometry. M .
[0113] 6) Test method for mass content of silicon in negative electrode materials: According to the measured mass content of carbon element in the negative electrode material m C 、Mass content of oxygen element m O And the mass content of element M is m M , calculate the mass content of silicon element, m Si =1-m C -m O -m M -m 水 .
[0114] 7) Lab color difference test method for negative electrode materials: The color difference test is completed using a Konica Minolta CM-5 colorimeter in the reflection mode, including mirror reflected light. The measurement result of this method includes all the surface reflected light of the object, and is independent of the structure and roughness of the surface of the object. The measurement result can reflect the true color of the object.
[0115] 8) Powder conductivity test of negative electrode material According to the equipment and methods of BTRTC / ZY / 02-093 "Powder Conductivity Test Operation Guide", the powder conductivity of the material is tested. The test equipment comes from Mitsubishi Chemical of Japan. The test parameters are: the initial resistance magnitude can be selected as -3, the voltage limit can be selected as 10V, and the sample quality must ensure that the sample thickness is 3~5mm under 20KN pressure. The pressure settings are 4, 8, 12, 16, and 20KN. The Electrode radius is 0.7mm and the Sample radius is 10mm.
[0116] 9) XRD test of negative electrode material: The negative electrode material was made into sheets and tested using an X-ray diffraction analyzer. Angle range: 10-90°, scanning mode: step scanning, select slit width 1.0, and set voltage 40kW and current 40mA. The measured data was analyzed using Jade 6.5 software to obtain the half-peak width of each characteristic peak.
[0117] 10) Raman data test XPLORA laser confocal Raman spectrometer was used to perform Raman testing on the negative electrode material. Samples were prepared according to the equipment standard and tested. Each sample was tested at 10 points at different locations to obtain the average intensity of the characteristic D peak and G peak of the negative electrode material and obtain I D / I G ratio.
[0118] 11) Test method for tap density of negative electrode material: Refer to GB / T 5162-2006 / ISO 3953:1993 "Determination of tap density of metal powders", and use the Quantachrome tap density analyzer (Quantachrome DAT-4-220) of Anton Paar (Shanghai) Trading Co., Ltd. for testing. The tap density T is the value after 3000 vibrations, and the unit is g / cm 3 .
[0119] 12) Testing method for carbon layer thickness: The material was sectioned using an ion mill and the average thickness of the carbon layer on the surface of the material was measured using a SEM.
[0120] 13) Test method for water mass content in negative electrode materials The moisture content was determined in accordance with GB / T 6283-2008 "Determination of Water Content in Chemical Products - Karl Fischer Method (General Method)", and the coulometric titrator (C30S-Inmotion KF) of Mettler-Toledo was used for moisture testing. A certain amount of sample was placed in a special dry glass bottle, and the sample was heated in the sample inlet tray of the coulometric titrator to evaporate the water into water vapor, which was then transferred to the titration cup of the titrator through dry carrier gas, reacted with Karl Fischer to the titration endpoint, and the moisture content was determined by the consumption of Karl Fischer reagent.
[0121] 14) Button battery test The prepared negative electrode material, conductive carbon black and polyacrylic acid binder were dissolved in a solvent at a mass percentage of 75:15:10, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet; a metal lithium sheet was used as a counter electrode and assembled into a button cell in an argon-filled glove box. The charge and discharge test was carried out at a current density of 0.1C and a charge and discharge interval of 0.01-1.5V.
[0122] Negative electrode material capacity test: Use button battery charging and discharging equipment, 0.1C constant current charging to 10mV, then 0.02C constant current charging to 5mV, 0.1C constant current discharge to 1.5V cutoff.
[0123] 50-week cycle test: using button cell charging and discharging equipment, in the first week, 0.1C discharge to 0.01V, 0.01C discharge to 0.01V, 0.01C discharge to 0.005V, 0.1C charge to 1.5V; in the second week, 0.2C discharge to 0.01V, 0.02C discharge to 0.01V, 0.02C discharge to 0.005V, 0.2C charge to 1.5V; in the third week, 0.5C discharge to 0.01 V, 0.05C discharge in equal steps to 0.01V, 0.05C discharge to 0.005V, 0.5C charge to 1.5V; from the 4th to the 50th week, 1C discharge to 0.01V, 0.1C discharge in equal steps to 0.01V, 0.1C discharge to 0.005V, 1C charge to 1.5V; in the 51st week, 0.1C discharge to 0.01V, 0.01C discharge in equal steps to 0.01V, 0.01C discharge to 0.005V.
[0124] 15) Electrochemical performance test The prepared negative electrode material is mixed with graphite in proportion to achieve a standard capacity of 450mAh / g; then mixed with sodium carboxymethyl cellulose CMC, binder styrene-butadiene rubber SBR, conductive agent Super-P, and conductive agent KS-6 in a mass ratio of 92:2:2:2 to form a slurry, which is coated on copper foil, and vacuum dried and rolled to prepare a negative electrode plate; then the ternary positive electrode plate prepared by traditional mature technology, 1mol / L LiPF6 / ethylene carbonate + dimethyl carbonate + methyl ethyl carbonate (v / v=1:1:1) electrolyte, Celgard2400 diaphragm, and shell are assembled into a CR2016 simulated battery using conventional production processes. The cycle performance test uses a constant current charge and discharge experiment with a current of 30mA, and the charge and discharge voltage is limited to 0~1.5V.
[0125] The LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. was used for testing. The capacity retention rate test was carried out at high temperature (60 degrees Celsius), and the charge and discharge test was carried out at a current density of 0.2C with a charge and discharge range of 2.75-4.2V.
[0126] First coulombic efficiency = first cycle discharge capacity / first cycle charge capacity.
[0127] Repeat the cycle for 50 times and use a micrometer to measure the thickness of the electrode of the lithium-ion battery. The thickness is H1. After 50 cycles, the expansion rate = (H1-H0) / H0×100%, and the initial thickness of the electrode is H0.
[0128] Repeat 100 cycles and record the discharge capacity as the remaining capacity of the lithium-ion battery; capacity retention rate = remaining capacity / initial capacity 100%.
[0129] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments. Within the scope of the unchanged main rights, appropriate changes can be made to the implementation.
[0130] Example 1 A method for preparing a negative electrode material comprises the following steps: (1) Use carbon-coated SiO y (y=1) material (carbon content 3%±0.1%), 1000g of powder with D50=6.0±0.3um was screened as a silicon oxide raw material, mixed with 100g of lithium carbonate as a dopant, placed in a sealed container, passed through argon protection, and stirred at a speed of 750 r / min for 180min.
[0131] (2) The mixture was sealed and placed in a high-temperature reactor. After sealing, argon protective gas was introduced. The first heating stage was carried out at a heating rate of 1°C / min. When the temperature gradient was 100°C-150°C-200°C-250°C, the temperature was maintained for 3 hours in each stage. The heating rate was continued to be maintained to 300°C and kept warm for 3 hours. Stirring was maintained throughout the process at a stirring rate of 1500 r / min. The powder solid phase pre-reaction was carried out in the second heating stage. Stirring was stopped in the second heating stage, and heating was continued. The heating rate was maintained at 1°C / min and the temperature was continued to rise to 980°C. After the temperature stabilized, heat treatment was carried out for 120 minutes, and the dopant gas was exhausted to obtain a pre-reaction product.
[0132] (3) The pre-reaction product is placed in a high-pressure package for high-pressure and high-temperature heat treatment. The pressure is set to 200 MPa, the heat treatment temperature is 1200°C, and the heat treatment time is 12 hours to obtain a precursor.
[0133] (4) Crush and break up the precursor. Prepare a surface impregnation liquid, dissolve the liquid asphalt in anhydrous ethanol, the added mass ratio of the liquid asphalt is 5%, stir and dissolve for 120 minutes, filter out impurities, and obtain a surface impregnation liquid. Add the broken up precursor powder to the impregnation liquid, control the material-liquid mass ratio to 1:1, stir at a speed of 3000 rpm for 90 minutes, let it stand for 24 hours after completion, and filter; use a vacuum oven to dry the filtered material at 90°C for 24 hours to obtain a composite.
[0134] (5) The composite is subjected to vacuum PECVD to carbonize the organic carbon source. Specifically, xylene is dissolved in ethanol at a mass ratio of 1:1 to prepare a coating solution, and the coating solution is preheated at 85°C to obtain a liquid coating solution containing benzene. After evacuation, argon gas is introduced into the cavity at a flow rate of 200sccm, and the pressure in the cavity is controlled at 5000Pa by a vacuum valve. After the liquid coating solution is wrapped onto the surface of the composite by PECVD, the temperature is raised to 600°C, and the deposition time is 2.0h after the temperature and pressure are stabilized; the product is then broken up and screened, vacuum dried after evacuation, and packaged under inert gas protection to obtain the negative electrode material.
[0135] Example 2 The difference from Example 1 is: (1) Use carbon-coated SiO y (y=1) material (carbon content 3%±0.1%), screen 1000g of powder with D50=6.0±0.3um as silicon oxide raw material, mix it with 50g of magnesium powder, put it in a sealed container, pass argon gas protection, and stir it at a speed of 750 r / min for 180min.
[0136] Example 3 The difference from Example 1 is: (1) Use carbon-coated SiO y (y=1) material (carbon content 3%±0.1%), screen 1000g of powder with D50=6.0±0.3um, as the silicon oxide raw material, mix it with 54g of aluminum powder and 14g of lithium powder, put it in a sealed container, pass argon gas for protection, and stir it at a speed of 750r / min for 180min.
[0137] Example 4 The difference from Example 1 is: (3) The pretreated material is placed in a high pressure package for high pressure and high temperature treatment. The pressure is set to 150 MPa, the heat treatment temperature is 1200°C, and the heat treatment time is 12 hours to obtain a precursor.
[0138] Example 5 The difference from Example 1 is: (3) The pretreated material is placed in a high pressure package for high pressure and high temperature treatment. The pressure is set to 100 MPa, the heat treatment temperature is 1200°C, and the heat treatment time is 12 hours to obtain a precursor.
[0139] Example 6 The difference from Example 1 is: (3) The pretreated material is placed in a high pressure package for high pressure and high temperature treatment. The pressure is set to 200 MPa, the heat treatment temperature is 800 °C, and the heat treatment time is 18 hours to obtain a precursor.
[0140] Example 7 The difference from Example 1 is: (5) The composite is subjected to vacuum PECVD to carbonize the organic carbon source. Specifically, benzene is dissolved in ethanol at a mass ratio of 1:1 to prepare a coating solution, and the coating solution is preheated at a preheating temperature of 85°C to obtain a liquid coating solution containing benzene. After evacuation, argon gas is introduced into the cavity at a flow rate of 200sccm, and the pressure in the cavity is controlled at 5000Pa by a vacuum valve. After the liquid coating solution containing benzene is wrapped onto the surface of the composite by PECVD, the temperature is raised to 550°C, and the deposition time is 1.5h after the temperature and pressure are stabilized; the product is then broken up and screened, vacuum dried after evacuation, and packaged under inert gas protection to obtain the negative electrode material.
[0141] Example 8 The difference from Example 1 is: (5) The composite is subjected to vacuum PECVD to carbonize the organic carbon source. Specifically, phenol is dissolved in ethanol at a mass ratio of 1:1 to prepare a coating solution, and the coating solution is preheated at 85°C to obtain a liquid coating solution containing phenol. After evacuation, argon gas is introduced into the cavity at a flow rate of 200sccm, and the pressure in the cavity is controlled at 5000Pa by a vacuum valve. After the liquid coating solution is wrapped onto the surface of the composite by PECVD, the temperature is raised to 400°C, and the deposition time is 2.0h after the temperature and pressure are stabilized; the product is then broken up and screened, vacuum dried after evacuation, and packaged under inert gas protection to obtain the negative electrode material.
[0142] Example 9 The difference from Example 1 is that in step (1), carbon-coated SiO material (carbon content 3%±0.1%) is selected, 1000 g of powder with D50=6.0±0.3 um is screened as the silicon oxide raw material, mixed with 25 g of lithium powder, and stirred at 750 r / min for 180 min in a sealed container under argon protection.
[0143] In step (3), a high pressure and high temperature heat treatment is performed at a temperature of 800° C. for 6 hours to obtain a precursor.
[0144] Comparative Example 1 A method for preparing a negative electrode material comprises the following steps: (1) Use carbon-coated SiO y (y=1) material (carbon content 3%±0.1%), 1000g of powder with D50=6.0±0.3um was screened as a silicon-based raw material, mixed with 100g of lithium carbonate, placed in a sealed container, passed through argon protection, and stirred at a speed of 750 r / min for 180min.
[0145] (2) The mixed materials are sealed and placed in a high-temperature reactor. After sealing, argon protective gas is introduced, and the temperature is raised to 300°C at 1°C / min and kept at this temperature for 3 hours to carry out the solid phase pre-reaction of the powder. Stirring is maintained throughout the reaction at a stirring rate of 1500r / min. After the heat treatment is completed, stirring is stopped and heating is continued at a heating rate of 1°C / min to 1200°C. After the temperature stabilizes, heat treatment is carried out for 120 minutes.
[0146] (3) The pretreated material was treated with methane as a gas phase carbon source, heated to 900°C for carbon coating for 5 hours, and the methane flow rate was set to 500 sccm. The carbon-coated product was then broken up and sieved, vacuum dried, and packaged under inert gas protection to obtain the negative electrode material.
[0147] Comparative Example 2 The difference from Example 1 is: (3) The pre-reaction product of step (2) is heat treated at normal pressure at a temperature of 600° C. for 12 hours; the heat treated product is then broken up and sieved, vacuum dried, and packaged under inert gas protection to obtain a negative electrode material.
[0148] Comparative Example 3 The difference from Example 1 is: In step (1), no dopant is added, that is, step (2) is directly carried out using the silicon oxide raw material.
[0149] The negative electrode materials prepared in the examples (abbreviated as S1 to S9) and the comparative examples (abbreviated as D1 to D3) were subjected to performance tests. The results of the above performance tests are shown in Tables 1 and 2: Table 1. Summary of performance test results of negative electrode materials
[0150] Table 2. Summary of performance test results of negative electrode materials
[0151] According to the data in Tables 1 and 2, by controlling the color difference parameters of the negative electrode material and cooperatively controlling the ratio of the half-peak width of the strongest characteristic peak of the metal M compound in the negative electrode material to the half-peak width of the characteristic peak of silicon in the negative electrode material within the range of 0.2 to 0.8, the mass proportion of the metal M compound in the silicon-based active material can be adjusted. Since the metal M compound is inert, under the synergistic effect of an appropriate amount of the metal M compound and the carbon material on the surface of the silicon-based active material, the side reaction between the silicon-based active material (especially silicon and silicon oxide) and the electrolyte can be reduced, the consumption of active lithium ions can be reduced, the interface stability of the negative electrode material in contact with the electrolyte can be enhanced, the first coulomb efficiency and specific capacity of the negative electrode material can be improved, and the expansion efficiency of the negative electrode material can be reduced.
[0152] According to Examples 1 to 3 and Comparative Example 3, the chromaticity of the negative electrode materials prepared by different doping metals is different. The Lab three values of the negative electrode materials containing metal M compounds are generally higher than those of the negative electrode materials containing silicon oxides. In addition, as the mass content of carbon in the negative electrode material increases, the carbon layer on the surface of the silicon-based active material will gradually thicken. 3 The molar proportion of hybridized carbon atoms is relatively large and the carbon material is mainly disordered structural carbon. The color of the carbon material is grayish, and the overall brightness of the negative electrode material will be improved. As the FWHM (M) / FWHM (Si) ratio increases, the metal M compound in the negative electrode material increases, and the capacity of the negative electrode material of Example 3 is slightly reduced compared with Example 1.
[0153] According to the test data of Examples 1 and 4-5, by adjusting the temperature, pressure and duration of the high temperature and high pressure heat treatment of the pre-reaction product, the high pressure treatment will change the crystal growth, especially the high pressure environment, which will inhibit the growth of grains to a certain extent, inhibit the diffusion and rearrangement of atoms, so as to control the core phase separation, the M element is in a dispersed state, and the lithium ion diffusion resistance decreases during the charge and discharge process, which is conducive to improving the capacity of the negative electrode material, and the silicon-based active material in the negative electrode material includes small silicon grains, small interface resistance, and high reversible capacity. As the pressure decreases, the crystalline phase in the core silicon-based active material is mainly silicon crystals and silicate grains, and the grains with different crystalline phases are separated, and the FWHM (M) / FWHM (Si) ratio decreases, the metal M compound of the negative electrode material decreases, and the mass proportion of silicon and silicon oxide increases. During the charge and discharge process, the electrons diffuse slowly inside the silicon particles of the large crystal core, resulting in a decrease in the first coulomb efficiency of the negative electrode material.
[0154] In Example 6, the duration of high temperature and high pressure heat treatment is increased, but due to the low temperature, silicates with irregular crystal forms may be formed. The XRD test shows that the main peak of the characteristic peak of silicates becomes a wide peak, the half-peak width is increased, and the FWHM (M) / FWHM (Si) ratio is increased compared with Example 1. However, due to the low temperature, silicon and silicates have not undergone complete structural rearrangement, and the diffusion of low surface energy silicates is insufficient. Therefore, the electrolyte has a higher probability of contacting active silicon during the charge and discharge process, and the first coulomb efficiency of the negative electrode material is slightly affected.
[0155] According to the test data of Examples 1 and 7-8, different benzene ring-containing carbon sources can effectively improve the surface defects of the negative electrode material, so that the chromaticity of the negative electrode material is within an appropriate range. This is because the molecular-level carbon source can be fully adsorbed on the surface defect vacancies and carbonized and deposited in situ, so that the color difference of the negative electrode material is within an appropriate range, and the first coulombic efficiency and specific capacity of the negative electrode material are also excellent.
[0156] It can be seen from the test data of Example 1 and Example 9 that the addition of lithium powder to pre-lithiate the silicon oxide raw material can improve the specific capacity of the negative electrode material. However, due to the low temperature of the high temperature and high pressure treatment, the degree of reaction between the solid phase components is reduced, resulting in the intensification of the side reaction between the negative electrode material and the electrolyte. The first coulombic efficiency and cycle performance of the negative electrode material are slightly reduced compared with Example 1.
[0157] According to the test data of Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 does not perform solid-phase pre-reaction, the precursor is locally doped with too much metal, the local heat release of metal M is aggravated when reducing silicon oxide, the silicon grain size increases, resulting in a decrease in the half-width of silicon, and the FWHM (M) / FWHM (Si) ratio is too large. The capacity of the negative electrode material decreases, and the defects and pores caused by metal M when reducing silicon oxide will also increase, which significantly increases the contact reaction sites between the negative electrode material and the electrolyte, aggravates the side reactions, and reduces the first coulombic efficiency of the negative electrode material.
[0158] According to the test data of Example 1 and Comparative Example 2, Comparative Example 2 does not use high pressure and high temperature treatment and carbon coating treatment, the uniformity of metal doping in the precursor decreases, and local enrichment is complete to form a variety of compounds including silicates and silicon oxides. The proportion of metal M compound components becomes lower, FWHM (M) decreases, and the FWHM (M) / FWHM (Si) ratio also decreases. The color difference of the negative electrode material is also significantly different from that of Example 1, which leads to the intensification of the side reaction between the negative electrode material and the electrolyte, the intensification of gas production during charging and discharging, and the decrease of the first efficiency, capacity and cycle stability of the battery.
[0159] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes a silicon-based active material and a carbon material located on at least a portion of the surface of the silicon-based active material, wherein the silicon-based active material includes at least one of silicon, silicon oxide and a metal M compound; Performing a Lab color difference test on the negative electrode material to obtain the brightness L, red-green color a, and yellow-blue color b of the negative electrode material, wherein 15≤L≤35, -2≤a≤5, and -2≤b≤5; In the XRD spectrum of the negative electrode material, the half-peak width of the strongest characteristic peak in the metal M compound in the negative electrode material is FWHM (M) , the half-peak width of the characteristic peak of the silicon (111) surface is FWHM (Si) , 0.2<FWHM (M) / FWHM (Si) <0.
8.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: (1)23.5≤L≤35; (2)-0.5≤a≤1.5; (3)-0.5≤b≤1.5。 3. The negative electrode material according to claim 1, characterized in that The metal M element includes at least one of Li, Mg, Al, Ti and Cu.
4. The negative electrode material according to claim 1, characterized in that FWHM (M) >0.2; and / or, FWHM (Si) >0.
2.
5. The negative electrode material according to claim 1, characterized in that The metal M compound comprises at least one of a metal silicide and a metal silicate; and / or The mass content of the metal M element in the negative electrode material is m M %,2.0≤m M ≤15.
6. The negative electrode material according to claim 1, characterized in that The negative electrode material is tested by X-ray photoelectron spectroscopy, and the surface of the negative electrode material has at least one oxygen-containing group selected from CO, C=O and COO-; and / or, the negative electrode material is tested by infrared spectroscopy, and the surface of the negative electrode material has at least one functional group selected from OH and CH.
7. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: (1) The silicon oxide comprises silicon and oxygen, and the atomic ratio of the silicon to the oxygen is 0 to 2, excluding 0; (2) The chemical formula of the silicon oxide is SiO x , where 0<x≤2; (3) The carbon material includes at least one of amorphous carbon and graphitized carbon.
8. The negative electrode material according to any one of claims 1 to 7, characterized in that The negative electrode material meets at least one of the following characteristics: (1) Median particle size D of the negative electrode material 50 4μm~9μm; (2) The specific surface area of the negative electrode material is 0.5 m 2 / g~3.0m 2 / g; (3) The powder conductivity of the negative electrode material under a pressure of 20KN is 0.2 S / cm~10.0S / cm; (4) The tap density of the negative electrode material is 0.75 g / cm 3 ~2.00g / cm 3 .
9. The negative electrode material according to any one of claims 1 to 7, characterized in that The negative electrode material meets at least one of the following characteristics: (1) The mass content of carbon in the negative electrode material is m C %,2≤m C ≤15; (2) The mass percentage of water in the negative electrode material is m 水 %,0.01≤m 水 ≤0.1; (3) The carbon material located on at least a portion of the surface of the silicon-based active material forms a carbon layer, and the thickness of the carbon layer is 50 nm to 1000 nm.
10. A battery, characterized in that: Comprising the negative electrode material as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Silicon-based composite, anode comprising same, and lithium secondary battery
CN112514116A
Negative electrode material, and electrochemical device and electronic device comprising same
CN113054167A
Negative electrode material, preparation method thereof and battery
CN117334859A
Evaluation method, electrode for electricity storage device, and electricity storage device
JP2020161771A
Carbon coated silicon material
WO2019150725A1
Cited By
Battery negative electrode, secondary battery, negative electrode material and preparation method of negative electrode material
CN120545327A
Negative electrode material and battery
WO2026129838A1
Negative electrode material and secondary battery
WO2026149360A1